1985
DOI: 10.1210/jcem-60-5-1025
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Furosemide with Serum Thyroxine Binding Sites: In Vivo and in Vitro Studies and Comparison with Other Inhibitors*

Abstract: The diuretic furosemide inhibits serum protein binding of T4 in equilibrium dialysis, dextran-charcoal, and competitive ligand binding separation systems and displaces [125I]T4 from isolated preparations of T4-binding globulin (TBG), prealbumin, and albumin. Equilibrium dialysis studies of undiluted normal serum showed that about 10 micrograms/ml furosemide increased the free T4 and free T3 fractions. Displacement occurred at lower drug concentrations in sera with subnormal albumin and TBG levels. Binding of [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 25 publications
0
11
0
3
Order By: Relevance
“…This allows us to demonstrate unequivocally that although cleavage of the reactive loop in TBG results in a markedly lowered affinity, the cleaved form still binds thyroxine with an affinity that greatly exceeds the binding affinity of intact uncleaved TBG for drugs such as furosemide that are considered to compete in vivo for binding with thyroxine (34). We also show here that cleaved CBG can still effectively complex with cortisol (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…This allows us to demonstrate unequivocally that although cleavage of the reactive loop in TBG results in a markedly lowered affinity, the cleaved form still binds thyroxine with an affinity that greatly exceeds the binding affinity of intact uncleaved TBG for drugs such as furosemide that are considered to compete in vivo for binding with thyroxine (34). We also show here that cleaved CBG can still effectively complex with cortisol (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Massive proteinuria may result in loss of thyroid-binding globulin (TBG) 29 and furosemide can compete for T4-binding sites on TBG, both contributing to lower total T4 and T3 levels. 30 While oxidative stress, psychological pressure and the long-term use of glucocorticoid can inhibit the expression of TSH in pituitary, balancing out the elevated TSH caused by the low levels of serum thyroid hormones, thus making the levels of serum TSH be normal or slightly low. [31][32][33] Yu et al 34 showed that the syndrome was due, in part, to the decreased activity of type I 5 0 -deiodinase (5 0 -DI), the hepatic enzyme that converts T4 to T3.…”
Section: Discussionmentioning
confidence: 99%
“…Schwankungen der Jodidzufuhr ausgleichen kann. [33,40,43,46] die Bindung. Auch angeborene TBG-Varianten füh-ren zu einer verminderten Bindungskapazität [23].…”
Section: Transport 5 Plasmatransportunclassified